(untitled) (World Bulletin of Management and Law, 2024)
The article describes the history of the concept of corruption, its impact on our society today, criminal consequences, the work being done to identify and expose them, and the experiences of foreign countries. At the same time, positive changes in the fight against corruption in the Republic of Uzbekistan were highlighted.